Reproduction and recruitment of the South American red shrimp, Pleoticus muelleri (Crustacea : Solenoceridae), from the Southeastern coast of Brazil - Castilho, Antonio Leao [UNESP]; Costa, Rogério Caetano da [UNESP]; Fransozo, Adilson [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP] (Taylor & Francis As, 2008)
Critical stock conditions for shrimps commonly exploited in southeastern Brazil have resulted in the targeting of other shrimp species such as Pleoticus muelleri. Descriptions of reproductive biology in penaeid species are essential to implement sustainable fishery techniques. Therefore, reproduction, recruitment, and size at sexual maturity of the shrimp P. muelleri were investigated off the coast of the state of São Paulo (23S), Brazil, from January 1998 through June 2003. Ovarian maturity was used to examine breeding in adult females. Recruitment was defined as the number of juveniles caught per standard trawl (CPUE) in each month and season of sampling. The entire sample comprised 8375 females and 3829 males. Sizes (carapace length) at onset of sexual maturity were 9.1 and 11.1 mm for males and females, respectively. Over 5.5 years, females with ripe gonads were found in every season, with the highest percentages from October to March (spring to summer). Juvenile shrimp occurred year-round. These findings suggest a continuous reproductive pattern for P. muelleri, with temperature as an environmental stimulus for the ovary development cycle. These data and the hypothesis of the intrusion of the South Atlantic Central Water mass, which lowers water temperature and raises plankton production, suggest that the main reproductive months extend from late spring to early summer. The classical paradigm of continuous reproduction at lower latitudes, with increased seasonality of breeding period at higher latitudes, seems to be followed by this species.
Keywords: Pleoticus muelleri; recruitment; reproduction; sexual maturity; Solenoceridae